AMALAN MUT'AH AL-TALAQ DALAM MASYARAKAT DI TIGA WILAYAH SELATAN THAILAND: The Practice of Mut'ah al-Talaq in Three Southern Provinces of Thailand - Samah, Mahamatayuding (Jurnal Syariah, 2015)
Among the concern towards women who have been divorced in Islam is the husband’s obligation to the wife compensation termed as mut‘ah. The payment is made to the wife according to her status and husband’s financial ability. Islamic Family Law as it is applicable in Thailand also provides the same to the divorced wives. However, to what extent this provision is implemented in the state is questionable. According to the field work done, it is found that many of wives have not claimed the mut‘ah because of their ignorance of such rights. It is therefore important to have an effort to make the wives aware of this right so that their financial position can be improved.